Triple-Layer Themes in ROA Literature: A Bibliometric Mapping and Research Agenda for ARDL Modeling Evidence in Indonesian Banking - Anggun Wida Prawira; Siti Mujanah; Achmad Yanu Alif Fianto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to map the literature on stagflation, fintech lending, and financial resilience in relation to Return on Assets (ROA) in the Indonesian banking sector, and to propose an ARDL-based research agenda for further development. Using a descriptive-quantitative approach, the bibliometric analysis employs tools such as Publish or Perish and VOSviewer to systematically map both global and domestic scientific publications. This analysis identifies key research trends, thematic linkages, and scholarly collaborations concerning macroeconomic stress, digital disruption, and banking performance. The study integrates bibliometric insights with ARDL-based econometric findings to examine both short- and long-term effects. Unlike previous studies that focus solely on partial variable relationships, this research provides a more holistic perspective by combining literature mapping with empirical modeling. The bibliometric analysis reveals three primary clusters: (1) Fintech Lending, which emphasizes the growth of digital financial services, with a focus on regulation and financial inclusion in the post-COVID-19 era; (2) Macroeconomic Dynamics, which explores stagflation, inflation, and GDP, with ARDL modeling applied for long-term analysis; and (3) Bank Profitability, which examines ROA, credit risk, and liquidity, highlighting the importance of banking resilience. While stagflation and ARDL are less frequently explored in current research, they remain critical in macroeconomic discussions. By combining fintech, financial stability, and macroeconomic factors, this study presents a valuable research direction, particularly for emerging economies like Indonesia.